Leveraging Multicast Primitives for Highly Available Replication in Drone Swarms - Nascimento, João Victor; Brito, André; Salvador, Ewerton; Chen, Jiayi; Onofre, Tassany; Lochin, Emmanuel; Silvestre, Guthemberg (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Drone swarms have emerged as promising robotic platforms to solve an increasing number of real-world problems. Yet, the design of fully distributed services atop drones remains challenging largely due to limitations in underlying network stacks. To address this, we make a case for highly available replication as a key building block for distributed computing in the face of ad hoc, lossy wireless networks. Our work leverages multicast primitives and Conflict-free Replicated Data Types (CRDTs) to improve replica synchronisation. Our emulation study indicates that state-of-the-art multicast primitives play an important role on data replication in drone swarms, highlighting a fundamental trade-off between synchronisation efficiency and communication overhead.